2012
DOI: 10.1587/transinf.e95.d.1684
|View full text |Cite
|
Sign up to set email alerts
|

On the Security of an Efficient and Secure Dynamic ID-Based Remote User Authentication Scheme

Abstract: SUMMARYIn 2009, Wang et al. proposed an efficient and secure dynamic ID-based remote user authentication scheme based on the one-way secure hash function. This letter demonstrates that Wang et al.'s scheme is still vulnerable to impersonation attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Therefore, they advanced a new scheme to strengthen the password authentication and provide mutual authentication in 2009. But many researches [22][23][24][25] made it clear that the improved scheme was vulnerable .In 2009, Chang, et al, [22,23] demonstrated that the scheme proposed by Wang wasn't efficient and secure because the attacker can be verified by the server and select an identity at his will. Then they provided a new scheme based on a smart card to complete the mutual authentication without any verified Table and they claimed that the scheme could provide untraceability and convenience of password update.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they advanced a new scheme to strengthen the password authentication and provide mutual authentication in 2009. But many researches [22][23][24][25] made it clear that the improved scheme was vulnerable .In 2009, Chang, et al, [22,23] demonstrated that the scheme proposed by Wang wasn't efficient and secure because the attacker can be verified by the server and select an identity at his will. Then they provided a new scheme based on a smart card to complete the mutual authentication without any verified Table and they claimed that the scheme could provide untraceability and convenience of password update.…”
Section: Introductionmentioning
confidence: 99%